2009
DOI: 10.1158/0008-5472.can-09-1132
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde Dehydrogenase–Expressing Colon Stem Cells Contribute to Tumorigenesis in the Transition from Colitis to Cancer

Abstract: Patients with chronic ulcerative colitis are at increased risk of developing colorectal cancer. Although current hypotheses suggest that sporadic colorectal cancer is due to inability to control cancer stem cells, the cancer stem cell hypothesis has not yet been validated in colitis-associated cancer. Furthermore, the identification of the colitis to cancer transition is challenging. We recently showed that epithelial cells with the increased expression of aldehyde dehydrogenase in sporadic colon cancer correl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
199
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(206 citation statements)
references
References 38 publications
3
199
0
1
Order By: Relevance
“…ALDH is a marker of CSCs and a predictor of drug resistance in multiple cancers. 32,33 We examined ALDH activity in RARa2 overexpressing ARP1 and OCI-MY5 cells using the fluorescent ALDH substrate Aldefluor and western-blot analysis. ALDH expression and activity significantly increased in RARa2 overexpressing ARP1 and OCI-MY5 compared with the control cells (Figure 2A-B).…”
Section: Increased Rara2 Expression Induces Stem Cell Characteristicsmentioning
confidence: 99%
“…ALDH is a marker of CSCs and a predictor of drug resistance in multiple cancers. 32,33 We examined ALDH activity in RARa2 overexpressing ARP1 and OCI-MY5 cells using the fluorescent ALDH substrate Aldefluor and western-blot analysis. ALDH expression and activity significantly increased in RARa2 overexpressing ARP1 and OCI-MY5 compared with the control cells (Figure 2A-B).…”
Section: Increased Rara2 Expression Induces Stem Cell Characteristicsmentioning
confidence: 99%
“…Tissues from patients with colon cancer were retrieved under pathological supervision with Institutional Review Board approval from the University of Michigan and the University of Florida as described previously (42).…”
Section: Methodsmentioning
confidence: 99%
“…Colon cancer stem cells were generated by isolating and enriching for highlevel aldehyde dehydrogenase (ALDH high ) spheres from colon cancer tumor cells obtained from patients with sporadic colorectal cancer (26,27,29,42). Isolated cells were cultured in serum-free media as described previously (26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies have suggested that increased ALDH activity might be a universal marker since it identifies CSCs in liver [42], colon [43], lung [44], melanoma [45], head and neck [46], prostate [47], bladder [48], thyroid [49], glioblastoma [50] and osteosarcoma [51]. The aldefluor assay is used to measure ALDH activity and also allow FACS sorting of ALDH +/high cells.…”
Section: Csc Biomarkers and Techniques Used To Identify And Isolate Themmentioning
confidence: 99%